Complexity analysis for recent ALOHA random access techniques in satellite communications. (23rd August 2020) - Zamoum, Selma; Lacan, Jérôme; Boucheret, Marie‐Laure; Dupe, Jean‐Baptiste; Gineste, Mathieu
Summary: In this paper, we study the the complexity of packet localization at reception, for recent synchronous Random Access (RA) techniques based on the protocol ALOHA for satellite communications. The promising CRDSA (Contention Resolution Diversity Slotted ALOHA) offers better throughput, in comparison to the traditional slotted ALOHA protocols, thanks to the use of Successive Interference Cancellation (SIC) along with multireplica transmission. MARSALA (Multi‐replicA decoding using corRelation baSed locALizAtion) is one of the many variants and enhancement schemes of CRDSA that have been proposed in the literature. It is applied to CRDSA each time a decoding deadlock situation is reached (when no packets can be retrieved by CRDSA). MARSALA first localizes the replicas of collided packets on a chosen reference time slot using correlations. Then it performs coherent signal combination of packet replicas prior to decoding. However, despite the good performance offered by MARSALA, its localization process adds a significant complexity to the receiver in terms of correlation operations. R‐SPOTiT (Random Shared POsition Technique for Interfered random Transmissions) mitigates this complexity by introducing a shared information between the receiver and each of the transmitters, about all potential packets' locations on the frame, without any additional signaling overhead. We focus in this paper on the analysis of the total number of correlations which are needed to localize packets' replicas for both MARSALA and R‐SPOTiT, with a single or with multiple Gold preambles. This should include preamble detection operations that are performed at CRDSA with a coarse and fine tracking. The results show that the most suitable system to use is the multi‐preamble R‐SPOTiT with two preambles. Abstract : R‐SPOTiT mitigates the complexity of localizing packets, compared to MARSALA, after CRDSA is blocked due to the shared information between the receiver and each of the transmitters, without any additional signaling overhead. The results show that the most suitable system to use is the multi‐preamble R‐SPOTiT with two preambles. Considering the number of data localization correlations and preamble detection, the complexity of R‐SPOTiT is on average four times lower than that of MARSALA.